Causing Factors of Urban Sprawl Symptoms in Peri-Urban Areas of Singaraja City, Bali Province - I Gede Wyana Lokantara; Farisa Maulinam Amo (P4W LPPM IPB, 2021)
The development of a city is marked by an increase in population and an increase in the need for space, which causes the city to be unable to accommodate its activities. Hence, physical development of the city to the peri-urban area and urban sprawl occurs. This also happened in Singaraja City, Bali province as proved by the increasing development of settlements in the area. The purpose of this research is to identify the development of Singaraja City spatially by looking at the pattern of city development due to the influence of the urban sprawl and to identify the factors that influence its development. This study used qualitative methods to analyze the spatial transformation through mapping techniques using time series data developed regions and non-woke Singaraja City, so discovered patterns development impact suburban of Singaraja City. It further analyzed the determinant factors causing urban sprawl in suburban Singaraja. The research shows that Singaraja City has experienced urban development towards the suburban of the city by forming a leap-frog development pattern. The suburban of Singaraja City that are most dominantly affected are the western and eastern regions, namely Baktiseraga Village and Banyuning district. The dominant factor that causes urban sprawl in suburban Singaraja City is people's desire to conduct commercial activities amounting to 94.67% with the opening of shops and services to facilitate the needs of students or migrant workers. The emergence of new economic activities initiated by the surrounding population, causing the orientation of economic transformation in the suburbs of Singaraja city to switch to the non-agricultural sector.